Radiologic Evaluation Criteria for Chronic Subdural Hematomas: Recommendations for Clinical Trials - McDonough, R.; Bechstein, M.; Fiehler, J.; Zanolini, U.; Rai, H.; Siddiqui, A.; Shotar, E.; Rouchaud, A.; Kallmes, K.; Goyal, M.; Gellissen, S. (American Journal of Neuroradiology, 2022)
SUMMARY: Embolization of the middle meningeal artery has gained substantial interest as a therapy for chronic subdural hematomas. For the results of the currently running chronic subdural hematoma trials to inform clinical practice, sufficient accuracy and matching definitions are necessary. We summarized the current practice in chronic subdural hematoma evaluation and derived suggestions on reporting standards using the Nested Knowledge AutoLit living review platform. On the basis of the most commonly reported data elements, we suggested a set of standardized image-based study end points for chronic subdural hematoma evaluation for future trials. The measurement methods and reporting standards as proposed in this article have been derived from published best practices and are endorsed by the European Society of Minimally Invasive Neurological Therapy’s research committee. The standardization of radiologic outcome measures and measurement techniques in chronic subdural hematoma embolization trials would increase the impact and implication of each trial as well as facilitate data pooling for increased statistical power and, therefore, translation to clinical practice.cSDHchronic subdural hematomaMLSmidline-shiftMLS-MMLS versus midline or displacement perpendicular to the midlineMLS-TMLS transverseMMAmiddle meningeal arteryNKNested KnowledgeSDHsubdural hematoma